Municipal councillors’ assessments of the usefulness of information generated by financial and budget statements - Magdalena Kowalczyk (Zeszyty Teoretyczne Rachunkowości, 2022)
Purpose: Entities from the public finance sector are required to function effectively. This translates significantly into the shape of public sector accounting. Achieving this goal requires relevant information, and the main sources of information about results are financial and budget statements, which are the basic products of accounting. This information is used by various users, including councillors, who are the decision-making and controlling body of communes. Therefore, the purpose of this study is to assess the usefulness of the information provided by financial and budget statements for management purposes from the point of view of councillors Method/approach: The article uses the survey method. A questionnaire was emailed to 800 councillors of rural, urban and urban-rural municipalities. The survey was conducted in 2020, and 65 completed questionnaires were received. Findings: The information provided by public sector accounting supports decision-making in municipalities. Both budget reports and financial reports are essential for management purposes. The annual report on the implementation of the budget is transparent for councillors, and the information contained therein allows for effective management of the finances of communes. Originality/value: The article provides information about the usefulness of financial and budget statements to the management of the commune. It shows the viewpoint of one group of stakeholders – councillors.